Desarrollo de un Sistema de Cultivo Tisular Híbrido y Multicomponente Usando Polímeros de Soporte Impresos 3D - Romero Zepeda, Claudia; Solorio González, Erick; Yépiz Rodríguez, María Antonieta; García, Alejandro; Chairez Oria, Jorge Isaac (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The development of different types of Organ on a Chip has attract the attention of pharmaceutical industry to develop alternative methods for ensuring the efficiency of drugs before approval. A dual bioprinting-culturing system was developed to construct the needed elements needed for creating three dimensional tissues including the corresponding instrumented device that may keep the environment conditions that may reinforce the cells´ growth. The proposed 3D printing platform considering the principles of an Organ on a Chip for the creation of a hybrid system of scaffolds for tissue engineering using polylactic acid. The usage of the 3D printing method allows the modification and creation of a flexible platform with different structures to a low cost, including the possibility of introducing the structural elements to create multi component tissues. The developed system was tested using a traditional fibroblasts culture.